Real time 3D O-arm based extremity bone tumour surgery - Vaibhav Sahu; Himanshu Rohela; Sunil Pasricha; Anila Sharma; Anurag Mehta (Journal of Orthopaedic Reports)
Background: Aneurysmal bone cyst (ABC) within the diaphyseal cortex is a very rare finding because most of the ABCs are of metaphyseal origin and within medullary cavity. Imaging of the cortical ABC may be inconclusive; therefore role of biopsy is extremely crucial in pre-operative period for the proper management and surgical plan. Case report: A 59-year-old female came to us with complaints of pain and swelling right arm since last 6 months. Radiograph of the involved arm was suggestive of cystic intracortical lesion without fracture. Core needle biopsy report came out to be aneurysmal bone cyst. O-arm and Computer navigation assisted en-bloc resection of the lesion was done as it was involving around half of the cortex and there was risk of iatrogenic fracture in intraoperative and postoperative period if done without navigation. Conclusion: O-arm provides real time 3D images which were quite helpful in navigation assisted resection of the lesion so that negative margins can be obtained and maximum cortex of the bone can be saved.